2014
DOI: 10.1267/ahc.14005
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Localization of α-amylase in the Submandibular and Sublingual Glands of Mice

Abstract: In the major salivary glands of mice, acinar cells in the parotid gland (PG) are known to be the main site for the production of the digestive enzyme -amylase, whereas -amylase production in the submandibular gland (SMG) and sublingual gland (SLG), as well as the cell types responsible for -amylase production, has been less firmly established. To clarify this issue, we examined the expression and localization of both the mRNA and protein of -amylase in the major salivary glands of male and female mice by quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
3
10
0
Order By: Relevance
“…It is the first enzyme that begins the process of digestion by breaking complex carbohydrate. Interestingly, it was believed that AMY1 was produced by ductal cells in mouse submandibular glands until the recent study detecting its strong expression in the acinar cells of parotid and weaker expression in submandibular glands of mice [37]. In our present study, we found for the first time that MIST1 alone can upregulate AMY1 expression in mMSCs.…”
Section: Discussionsupporting
confidence: 58%
“…It is the first enzyme that begins the process of digestion by breaking complex carbohydrate. Interestingly, it was believed that AMY1 was produced by ductal cells in mouse submandibular glands until the recent study detecting its strong expression in the acinar cells of parotid and weaker expression in submandibular glands of mice [37]. In our present study, we found for the first time that MIST1 alone can upregulate AMY1 expression in mMSCs.…”
Section: Discussionsupporting
confidence: 58%
“…30 It was observed that the parotid gland in the experimental group showed multifocal clusters of mononuclear inflammatory cells, but with maintenance of normal histological structure and the submandibular and sublingual glands showed no significant change 50 days after infection.…”
Section: Discussionmentioning
confidence: 82%
“…PTA preferentially stains proteins as shown by experiments with protein crystals (Maruyama et al, ) and cultured cells (Nishiyama et al, ). Therefore, the cell is considered to be a serous Demilune (Yamagishi et al, ), since these cells are known to have characteristic protein‐rich secretory granules.…”
Section: Resultsmentioning
confidence: 99%